Incentives for Effective Risk Management - Jón Daníelsson; Bjørn N. Jorgensen; Casper G. de Vries (Tinbergen Institute, 2001)
Under the new Capital Accord, banks choose between two different types of risk management systems, the standard or the internal rating based approach. The paper considers how a bank's preference for a risk management system is affected by the presence of supervision by bank regulators. The model uses a principal–agent setting between a bank's owner and its risk management. The main conclusion is that previously unregulated institutions can be expected to switch to the lower quality standard approach subsequent to becoming regulated, i.e., the presence of regulation may induce a bank to decrease the quality of its risk management system.
Keywords: G21; G28; 330; Risk management systems; Regulation; Value-at-Risk; Basel-II; Risikomanagement; Kreditrisiko; Bankenaufsicht; Basler Akkord